Laser Irradiation Effects in Simulated Laser-Assisted Machining of Type 316L SS - Agostino Maurotto; Fabio Scenini; Bjoern Kraemer (Journal of Manufacturing and Materials Processing, 2018)
Laser surface heating allows for the thermal treating of clearly defined surface areas thanks to the ability to focus the laser beam to a specific point. Thus, the rapid heating and subsequent rapid cooling when the beam is moved away, typically associated with laser light, is used as an in-machine process to improve the machinability of hard- or difficult-to-machine alloys. In laser-assisted machining (LAM), laser irradiation occurs simultaneously with materials removal; however, it is difficult to ensure a complete removal of the irradiated areas. In the present work, the two processes were decoupled to investigate the interaction effects of laser radiation type 316L. The surface residual stress, hardness, and microstructure of milled flat specimens were measured prior to and after diode-generated laser beam irradiation. Laser exposure of samples was conducted under protective gas shielding (Argon) using heating parameter combinations that would limit or avoid laser surface melting. Conversely, when the surface underwent melting, the formation of a fast solidification layer resulted in the removal of the cold-worked effect and the significant softening of the surface layers. Beam power density in-homogeneities and incomplete machining of the treated areas in LAM have the potential to introduce significant undesired changes on components’ surface integrity.